Investigation of calcium silicate as a natural clay‐based sunblock: Formulation and characterization. Issue 1 (3rd October 2020) - Abbas, Naseem; Manzoor, Suryyia; Saeed, Saira; Husnain, Syed Muhammad; Tariq, Muhammad; Akhtar, Zeeshan; Saira, Naveeda; Yasmin, Ghazala
Abstract: Background: Sunlight exposure causes several types of health issues to humans, and in particular, it affects especially the skin. Among the most common harmful issues developed by UV exposure are erythema, pigmentation, and lesions in DNA, which may lead to cancer. These long‐term effects can be minimized with the use of sunscreen. Objective: The use of commercial UV filters causes severe side effects such as skin allergy and whitening of the skin. Therefore, in this study the effectiveness of Ca2 SiO4, a compound abundantly present in the soils of certain South Asian regions, has been the first time explored as UV filter. This compound leaves a low amount of white residue on the skin and is highly stable. Method: The comparative study of a cosmetic formulation having 5% Ca2 SiO4, and other formulations containing 5% TiO2 and 5% ZnO as inorganic UV filters, was performed to evaluate the physical and chemical stability. Result: The zeta potential and chemical stability of formulations containing these different UV filters were investigated by using UV‐Vis spectroscopy, FTIR‐ATR, and X‐ray diffraction. Results indicated Ca2 SiO4 as a promising innovative UV filter with an SPF value of 37.94. One of the reasons is its low interaction with organic filter, that is, PABA, as compared to commercial ZnO and TiO2 inorganic UV filters. Biological absorption in organs was studied by ICP‐MS on model mice. Conclusion: It also has a low photocatalytic activity; thus, formation of radicals is minimum. Moreover, Ca2 SiO4 showed a recognized ability to leave a low amount of white residue on the skin combined with great stability.